Oryctolagus cuniculus - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Oryctolagus cuniculus (Linnaeus 1758) [Lepus] cuniculus Linnaeus 1758, Syst. Nat., 10th ed., Vol. 1: 58. Type Locality: "in Europa australis" [= Germany; Ellerman and Morrison-Scott, 1951]. Vernacular Names: European Rabbit. Synonyms: Oryctolagus borkumensis Harrison 1952; Oryctolagus campestris (Meyer 1790); Oryctolagus nigripes Bartlett 1857. Subspecies:: Subspecies Oryctolagus cuniculus subsp. cuniculus Linnaeus 1758 Subspecies Oryctolagus cuniculus subsp. algirus Loche 1858 Subspecies Oryctolagus cuniculus subsp. brachyotus Trouessart 1917 Subspecies Oryctolagus cuniculus subsp. cnossius Bate 1906 Subspecies Oryctolagus cuniculus subsp. habetensis Cabrera 1923 Subspecies Oryctolagus cuniculus subsp. huxleyi Haeckel 1874 Distribution: W and S Europe through the Mediterranean region to Morocco and N Algeria; original post-Pleistocene range probably limited to S France, Iberia and NW Africa, but Late Pleistocene records occur from Ireland to Italy, Hungary, and even W Siberia (Kurtén, 1968); introduced on all continents except Antarctica and Asia; see Gibb (1990). Worldwide as domesticated forms. Conservation: IUCN – Lower Risk (lc); considered a pest species in most areas where it has been introduced. Discussion: The specific name may be based on a feral specimen (Gibb, 1990). Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Lagomorpha, pp. 185-211 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 205, DOI: 10.5281/zenodo.7316519